2010
DOI: 10.1104/pp.110.160770
|View full text |Cite
|
Sign up to set email alerts
|

An Atlas of Type I MADS Box Gene Expression during Female Gametophyte and Seed Development in Arabidopsis

Abstract: Members of the plant type I MADS domain subfamily have been reported to be involved in reproductive development in Arabidopsis (Arabidopsis thaliana). However, from the 61 type I genes in the Arabidopsis genome, only PHERES1, AGAMOUS-LIKE80 (AGL80), DIANA, AGL62, and AGL23 have been functionally characterized, which revealed important roles for these genes during female gametophyte and early seed development. The functions of the other genes are still unknown, despite the fact that the available single T-DNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
116
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 45 publications
(107 reference statements)
13
116
0
Order By: Relevance
“…Moreover, seven type I MADS box genes are highly expressed in Arabidopsis embryo sac cells, including AGL23, AGL61, and AGL80, consistent with previously published data (Portereiko et al, 2006;Bemer et al, 2008;M. Colombo et al, 2008;Steffen et al, 2008).Complementing transcriptomic investigations, the expression pattern of 60 type I MADS box genes in Arabidopsis by translational reporter fusions was recently reported (Bemer et al, 2010). A total of 42 genes were detected in the female gametophytes or developing seeds, confirming their predominant involvement in plant reproduction.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, seven type I MADS box genes are highly expressed in Arabidopsis embryo sac cells, including AGL23, AGL61, and AGL80, consistent with previously published data (Portereiko et al, 2006;Bemer et al, 2008;M. Colombo et al, 2008;Steffen et al, 2008).Complementing transcriptomic investigations, the expression pattern of 60 type I MADS box genes in Arabidopsis by translational reporter fusions was recently reported (Bemer et al, 2010). A total of 42 genes were detected in the female gametophytes or developing seeds, confirming their predominant involvement in plant reproduction.…”
supporting
confidence: 71%
“…However, how AGL23 regulates chloroplast biogenesis is not clear since several pathways (e.g., carothenoid or lipid biosynthesis) could be under the control of AGL23. Expression studies showed that AGL23 expression correlates with the observed phenotypes since the putative AGL23 promoter drives GUS expression in the developing embryos at late globular stage when chloroplast biogenesis takes place and during embryo sac development as soon as the functional megaspore can be detected (M. .AGL23 shares high sequence similarity with AGL28, which is also expressed in developing embryos (Bemer et al, 2010 (Lee et al, 2000) upregulation, giving rise to the hypothesis that AGL28 plays a role in the autonomous flowering pathway (Yoo et al, 2006). However, homozygous agl28 mutant plants are viable, and no obvious aberrant phenotypes were observed (Yoo et al, 2006), making the suggested role for AGL28 in the regulation of flowering time premature.…”
mentioning
confidence: 99%
“…Also, the function of the different Type I genes is generally poorly characterized. However, several Type I genes have been reported to play a role in female gametogenesis, embryogenesis, and seed development (Portereiko et al, 2006;Bemer et al, 2010;Masiero et al, 2011).…”
Section: Iii2 Type I Mads-box Genesmentioning
confidence: 99%
“…S17), implicating a differential transcriptional regulation between embryo and endosperm. It was previously reported that TFs of MADS function in seed and endosperm development (Kang et al, 2008;Sreenivasulu et al, 2008;Bemer et al, 2010;Le et al, 2010;Agarwal et al, 2011;Hehenberger et al, 2012). AGL62, a MADS protein of Arabidopsis, is the direct target of FIS Polycomb group repressive complex2 (PRC2), establishing the molecular basis for FIS PRC2-mediated endosperm cellularization (Hehenberger et al, 2012).…”
Section: Differential Regulatory Mechanisms In Embryo and Endospermmentioning
confidence: 99%
“…Several TF family members are likely to play a role in cell fate determination, including C2C2-YABBY (GRMZM2G167824 and GRMZM2G529859) and GeBP (GRMZM2G036966) homologs, as well as in cell growth regulation and germination, including WRKY (Zhang et al, 2011a;GRMZM5G816457) and bHLH (GRMZM2G042920) homologs. On the other hand, the majority of TFs enriched in endosperm were families such as MADS, SBP, NAC, bZIP, Myb, and C2C2-GATA, most of which have been implicated in seed development (Sreenivasulu et al, 2008;Bemer et al, 2010;Le et al, 2010;Agarwal et al, 2011). A total of 33 TF genes were selected for confirmation of the differential expression between embryo and endosperm with real-time RT-PCR analysis.…”
Section: Survey Of the Gene Expression Regulators In Maize Seedmentioning
confidence: 99%